Effectiveness of Blended/Hybrid Cad Instruction (Online + Physical Hands-On) In Engineering Education (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The purpose of this research is to evaluate how blended or hybrid learning of CAD instruction serves the students of Manufacturing Engineering better. In engineering programs, with the acceleration of digital transformation in the post-pandemic era, online lectures and virtual demonstrations are increasingly combined with face-to-face laboratory activities to support design-based learning. This study used a descriptive comparative research approach and compared two groups: students who were enrolled purely in face-to-face CAD classes versus those enrolled in hybrid/blended classes. Academic statistics regarding student engagement, motivation, and satisfaction were collected using measurements of student performance combined with a student engagement survey. Hybrid learners performed marginally better than traditional learners on their course assessments and more significantly on final assessments and design projects. Student engagement measurements were consistently greater among hybrid students when compared with traditional students, indicating that the hybrid learning model, which integrates multimedia and flexible instructional approaches into the learning environment, enhances motivational and participatory aspects of learning. Feedback from surveys corroborates the impact of digital resources on students' ability to learn at their own pace and also notes issues related to internet connectivity and software limitations. Results provide strong support for the implementation of hybrid instructional formats in skills-based engineering courses (CAD). Hybrid instructional formats were noted to enhance cognitive and affective (motivational) learning outcomes of CAD.